Preventive and curative approaches to diaper dermatitis in children - Octarica, Stella Gracia (Acta dermatovenerologica Alpina, Pannonica et Adriatica, 2025)
Diaper dermatitis (DD) is a common inflammatory skin condition in the diaper area of infants, caused by a combination of host and environmental factors, such as moisture, friction, elevated skin pH, and prolonged exposure to urine and feces. This systematic review analyzed 13 studies involving 2,935 children to evaluate effective treatment and prevention strategies for DD. Key interventions identified include the use of disposable and emollient-containing diapers, gentle skincare practices (such as bathing every 1 to 2 days with mild cleansers and emollients), and pH-balanced wet wipes. Frequent diaper changes and allowing diaper-free time also help reduce skin irritation. Topical treatments, particularly emollients with zinc oxide or dexpanthenol, were found to be highly effective with minimal side effects. Preventive measures, such as using superabsorbent disposable diapers, regular application of barrier creams, and maintaining good hygiene, are crucial in reducing the incidence and severity of DD. In conclusion, a combined approach of proper diaper selection, gentle skincare, and judicious use of topical emollients is recommended for both treatment and prevention of DD in children.
Keywords: children; diaper dermatitis; dojenčki; infants; otroci; plenični dermatitis; preprečevanje; prevention; terapija; therapy